Lab assessment and discrete element modeling of asphalt mixture during compaction with elongated and flat coarse aggregates. (10th September 2018) - Gong, Fangyuan; Liu, Yu; Zhou, Xiaodong; You, Zhanping
Graphical abstract: Highlights: Analyze the influences of coarse aggregates' shapes on asphalt mixture compaction. Mixtures with 100% angular/fractured aggregates were easier to compact than hybrid. The larger ratio of elongated/flat aggregates, the worse compactability of mixtures. Abstract: Superpave gyratory compactor (SGC) is usually used for analysis of volumetric properties of asphalt mixture, evaluation of mixture densification properties, estimation of sensitivity to aggregates' shapes, field quality control and other testing purposes. The specimens produced by SGC very closely simulate the density, aggregate orientation and structural characteristics of asphalt mixture on actual pavement. Aggregates make up the major volume or mass of asphalt mixture, and their shapes significantly impact both the structural and mechanical performance of mixtures. The objectives of this study were to analyze the influences of selected coarse aggregates on asphalt mixture compaction through lab testing and modeling. First, coarse aggregates were classified into five types, and testing samples were produced with designed percentages of different types. Second, images of selected coarse aggregates were obtained by 3D scanning and saved in STL (Stereolithography) files. Finally, the air void curves and results of discrete element modeling (DEM) were used to evaluate the influences of selected coarse aggregate shapes on asphalt mixture compaction. It was found that the asphalt mixtures with 100% angular or 100% fractured coarse aggregates were easier to compact compared with asphalt mixtures of hybrid coarse aggregates in a SGC test. Results also clearly indicated that the larger percentage of elongated and flat aggregates, with a 3:1 ratio, results in worse compactability of asphalt mixtures under laboratory conditions, and the influences of flat aggregates were greater than that of elongated. Therefore, special attention should be paid to asphalt mixtures with a large percentage of elongated or flat aggregates.